Application of Fraser’s “Practical” Ethic in Veterinary Practice, and Its Compatibility with a “One Welfare” Framework - Fawcett, Anne (Animals (Basel), 2018)
SIMPLE SUMMARY: Ethically challenging situations are common in veterinary practice. Veterinary ethics is considered important by veterinary students, educators, and regulators alike, and may help to reduce stress arising from ethically challenging situations in veterinarians. Ethical frameworks are designed to aid ethical decision making, but some students may find theoretical ethical terminology off-putting and may struggle to apply frameworks to real-life decisions. Fraser’s “practical” ethic is a series of principles that can be applied in ethically challenging situations. We discuss the development of this approach and apply it to examples of ethically challenging situations that veterinarians may encounter. Because Fraser’s “practical” ethic acknowledges the interdependence of animal welfare, human well-being, and the environment, we argue that it is consistent with a One Welfare framework, adopted by organisations, such as the World Organisation for Animal Health (OIE). We describe the strengths and limitations of Fraser’s “practical” ethic, and the One Welfare framework, when employed in veterinary contexts, and recommend further training and support to enable veterinarians to effectively apply these frameworks. ABSTRACT: Ethically challenging situations are common in veterinary practice, and they may be a source of moral stress, which may in turn impact the welfare of veterinarians. Despite recognition of the importance of ethical reasoning, some veterinary students may struggle to apply theoretical ethical frameworks. Fraser developed a “practical” ethic consisting of four principles that can be applied to ethically challenging situations. We apply Fraser’s “practical” ethic to three cases that veterinarians may encounter: animal hoarding, animal neglect, and treatment of wildlife. We argue that Fraser’s “practical” ethic is consistent with a One Welfare framework, and may have increasing currency for veterinarians in the light of the World Animal Health Organisation’s Global Animal Welfare Strategy. Both Fraser’s “practical” ethic and a One Welfare framework require veterinarians to consider the impacts of animal ethics decisions on a broader scale than most other ethical frameworks have prepared them for. We discuss the strengths and limitations of Fraser’s “practical” ethic when applied in veterinary contexts and recommend additional support and training to enable veterinarians to effectively apply these frameworks in real-world settings.